2021
DOI: 10.1002/slct.202100206
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Yamaguchi Method to Esterification and Macrolactonization in Total Synthesis of Bioactive Natural Products

Abstract: Yamaguchi protocol provides functionalized esters regioselectively from carboxylic acids and alcohols employing 2,4,6trichlorobenzoyl chloride as the condensation reagent in the presence of a stoichiometric amount of 4-N,N-dimethylaminopyridine. The key features of this method comprise a high yield of esters, short reaction time, mild conditions, macrocyclic lactone ring formation, and regioselective preparation of highly functionalized esters. Such beneficial quality of this method as a whole have motivated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 182 publications
0
10
0
Order By: Relevance
“…The ligand 1,2-Di((9H-carbazol-9-yl)propanoyl)-sn-glycero-3-phosphocholine (DCzGPC) is synthesized in a one-step-synthesis via Yamaguchi esterification 22,23 of 3-Carbazol-9-yl-propionic acid (CzPA) and sn-Glycero-3-phosphocholine (GPC) (Fig. 1A The absorption of DCzGPC (dotted black line in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ligand 1,2-Di((9H-carbazol-9-yl)propanoyl)-sn-glycero-3-phosphocholine (DCzGPC) is synthesized in a one-step-synthesis via Yamaguchi esterification 22,23 of 3-Carbazol-9-yl-propionic acid (CzPA) and sn-Glycero-3-phosphocholine (GPC) (Fig. 1A The absorption of DCzGPC (dotted black line in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently,t he computational analysis supports our initial hypothesis that the pentafluorophenyl group is asuperior promoter for macrolactonization as it increases the electrophilicity of the relevant carbonyl group and has the potential to pre-organize the substrates through lp-p interactions.T hose results also explain why in the methods developed by Yamaguchi and Shiina, 4-dimethylaminopyridine (DMAP) is typically required as an acyl transfer reagent to compensate for the lack of electrophilicity of the mixed anhydride and to enable the macrolactonization, which is not necessary with our method. [3,4]…”
Section: Dft Studiesmentioning
confidence: 99%
“…In the seventies,ag roundbreaking discovery by Yamaguchi revealed that the stoichiometric activation of the carboxylic acid via the formation of amixed anhydride from 2,4,6-trichlorobenzoylchloride (TCBC), could be used as ad riving force to promote macrocyclizations. [3] This approach was further improved by Shiina with the development of the 2-methyl-6-nitrobenzoic anhydride (MNBA) reagent and related compounds. [4] Other classic examples based on the same concept include Corey-Nicolaou, [5] Steglich-Keck-Boden [6] and Mukaiyama macrolactonizations.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional approaches include the use of seco-acids via either activation of acid or activation of alcohols toward the synthesis of macrolactones. These approaches mainly focus on Yamaguchi reaction, Shiina macrolactonization, Corey–Nicolaou strategy, Stenglich–Boden–Keck reaction, use of Mukaiyama salt, use of pentafluorobenzoyl chloride, and ynamide mediated macrolactonization through activation of the carboxylic acids (Figure A). In contrast, the Mitsunobu reaction proceeds through the activation of alcohol (Figure A).…”
mentioning
confidence: 99%